2015
DOI: 10.1016/j.jgo.2014.09.184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yoga on cancer-related fatigue and global side-effect burden in older cancer survivors

Abstract: Background Sixty percent of cancer survivors are 65 years of age or older. Cancer and its treatments lead to cancer-related fatigue and many other side effects, in turn, creating substantial global side-effect burden (total burden from all side effects) which, ultimately, compromises functional independence and quality of life. Various modes of exercise, such as yoga, reduce cancer-related fatigue and global side-effect burden in younger cancer survivors, but no studies have specifically examined the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 31 publications
1
49
0
1
Order By: Relevance
“…Complementary therapies, such as massage therapy, 96,97,100 yoga, 101105 muscle relaxation, and stress reduction based on mindfulness, 106108 have been evaluated alone or in combination with CBT approaches. The data suggest that these therapies may be effective in reducing fatigue in patients with cancer.…”
Section: Interventions For Patients On Active Treatmentmentioning
confidence: 99%
“…Complementary therapies, such as massage therapy, 96,97,100 yoga, 101105 muscle relaxation, and stress reduction based on mindfulness, 106108 have been evaluated alone or in combination with CBT approaches. The data suggest that these therapies may be effective in reducing fatigue in patients with cancer.…”
Section: Interventions For Patients On Active Treatmentmentioning
confidence: 99%
“…Four trials tested the effects of yoga on CRF among cancer patients receiving chemotherapy or radiotherapy [43, 45, 51, 56]. Ten trials investigated the efficacy of yoga for treating CRF among survivors post-chemotherapy and/or post-radiation therapy [39, 41, 44, 49, 50•, 5255, 57•]. Two studies recruited both cancer patients and survivors [21, 26].…”
Section: Yoga For Treating Cancer-related Fatigue (Crf)mentioning
confidence: 99%
“…Interventions ranged in length from four weeks to six months. Eight studies showed that yoga significantly reduced CRF post-intervention and/or during 1-, 3-, or 6-month follow-ups comparing to the non-yoga intervention control groups where participants followed their standard cancer care only [41, 44, 49, 52, 57•] or received a health education intervention [39, 45, 50•]. Another two studies compared yoga to conventional strengthening exercises [51, 53] and found both groups significantly improved in multiple domains of fatigue.…”
Section: Yoga For Treating Cancer-related Fatigue (Crf)mentioning
confidence: 99%
“…Ronald Maggiore (Health Science University, Oregon, USA) explained how treatment is being tailored to the circumstances of individual patients through a combined oncogeriatric approach, assessment of life expectancy, and optimization of agents and drug dose using tools to predict chemotherapy-associated toxicity 14 . Long-term survivors face complex problems and require the support, among others, of therapists expert in speech, swallowing, hearing and nutrition.…”
Section: Local Initiatives Reflecting a Global Problemmentioning
confidence: 99%
“…The G8 screening tool described above contains questions about nutrition, weight loss and body mass index (BMI) 10 . And data from the MiniNutritional Assessment are among the clinical factors included by Extermann et al 14 in the CRASH score that predicts toxicity from cancer therapy. Superimposed on sarcopenia, the hypercatabolic state induced in advanced cancer by inflammatory mediators causes depletion of fat and muscle reserves that is resistant to conventional nutritional interventions.…”
Section: Supportive Carementioning
confidence: 99%